A new species of Boshkerria and redescription of B. punctata (Boshell and Kerr) (Trombidiformes: Trombiculidae) - Bassini-Silva, Ricardo (2021)
The Neotropical chigger genus Boshkerria includes, B. tuberculata and B. punctata, both species parasites mammals in Central and South America. Here, we redescribe B. punctata based on a lectotype and paralectotype designated herein and describe a new species, Boshkerria erwini n. sp., from the green acouchi Myoprocta pratti in Peru. Also, we provide a key to the three species in this genus. http://www.zoobank.org/urn:lsid:zoobank.org:act:8FE7E5ED-262A-4843-9BCF-D1A4E44D9B7C.